Entrepreneurship and geography—some thoughts about a complex relationship - Rolf Sternberg (The Annals of Regional Science, 2021)
This review article sheds a light on the complex and hitherto under-researched relationship between geography and entrepreneurship. This relationship is considered to be interdependent. Both directions are discussed. The paper also describes the perspectives of both academic disciplines involved in regional entrepreneurship research, namely (geographically sensitive) economics and management studies on the one hand, and economic geography on the other. Based on a comprehensive overview of the theoretical and empirical literature on regional entrepreneurship, several research gaps are identified that could be helpful for designing future research. Some have strong relevance for government policy, which has recently paid much more attention to entrepreneurship than in the past (e.g. related to the entrepreneurial ecosystem approach), but which rather rarely has been considered in academic evaluations so far. This paper ends with a suggestion for an agenda for future regional entrepreneurship research. Digital transformation with its potential for a disruptive transformation of economies and societies will provide an excellent and, of course, a currently not well-understood research field for regional entrepreneurship research.
Keywords: R19; L26; R11; 500